AB1091 Treatment Persistence with Subcutaneous Biologic Therapies in Patients with Rheumatoid Arthritis. (10th June 2014) - Lyu, R.; Govoni, M.; Ding, Q.; Fan, T.; Ogbonnaya, A.; Donga, P.; Korn, J.; Makin, C.
Abstract : Background: Subcutaneous biologic therapies are usually prescribed to patients with moderate to severe Rheumatoid Arthritis (RA), particularly in patients whose condition is not responding to conventional disease-modifying antirheumatic drugs (DMARDs). Objectives: The objective of this study was to describe treatment persistence over 12 months for RA patients who were newly treated with subcutaneous biologics, and assess differences between patients with and without prior DMARDs experience. Methods: A retrospective cohort study was conducted using the Electronic Medical Record database of IMS Disease Analyzer-Germany. Patients who were ≥18 years old, had at least one ICD-10 diagnosis code of RA during the study period, and had exposure to a subcutaneous biologic (certolizumab, etanercept, adalimumab, anakinra, or golimumab) between January 1, 2009 and June 30, 2012 were selected, with the first prescription date serving as the index date. Patients were required to have continuous observation for a minimum of 12 months prior to and after the index date. Patients with a prescription for any biologic (subcutaneous or intravenous) during the pre-index period, and/or those diagnosed with ankylosing spondilitis, psoriatic arthritis or other conditions treated with subcutaneous biologics either pre- or post-index were excluded from the study population. Persistence with any subcutaneous biologic agent was defined in consecutive days from treatment initiation until treatment discontinuation (continuous ≥60-day lapse in medication coverage). Patients were stratified into one of two mutually exclusive cohorts, based upon pre-index use (or lack thereof) of DMARDs. A chi-square test was used to measure the difference in the percentage of persistent patients and a logistic regression model was created to assess differences in the likelihood of being persistent, controlling for baseline demographic and clinical characteristics. Results: A total of 576 RA patients without biologic experience during the pre-index period were selected, 471 with prior DMARDs use and 105 without. The mean (SD) age of the patients was 57 (13) years, with 75% being female. The most frequent comorbidities were hypertension (10%), osteoporosis (9%), and diabetes (6%). Majority of the patients were treated with etanercept (46%) and adalimumab (40%). Overall a mean of 246 days on subcutaneous biologic treatment over a period of 12 months was observed. About 52% of the patients persisted on any biologics for at least 12 months. A significantly higher percentage of patients with pre-index DMARDs were persistent (56% vs. 33%; p=0.0001), and after controlling for pre-index characteristics, patients with a pre-index DMARDs had 2.49 times the odds of being persistent compared to those without pre-index DMARDs use (OR: 2.49, 95% CI: 1.54-4.04). Conclusions: More than half of the patients were persistent over 12 months after newly initiating their index subcutaneous biologic in Germany. Patients with pre-index DMARDs were significantly more likely to persist on biologic treatment than patients without pre-index DMARDs. Further investigation is needed to understand whether specific drugs have different persistence patterns. Disclosure of Interest: R. Lyu Employee of: Merck & Co. Inc, M. Govoni Employee of: Merck Sharp & Dohme Limited, Q. Ding: None declared, T. Fan Employee of: Merck & Co. Inc, A. Ogbonnaya Grant/research support: Merck & Co. Inc, P. Donga Grant/research support: Merck & Co. Inc, J. Korn Grant/research support: Merck & Co. Inc, C. Makin Grant/research support: Merck & Co. Inc DOI: 10.1136/annrheumdis-2014-eular.4656